The empowering variability of affordances of nature: Why do exercisers feel better after performing the same exercise in natural environments than in indoor environments?. (May 2019) - Araújo, D.; Brymer, E.; Brito, H.; Withagen, R.; Davids, K.
Abstract: Objectives: Evidence suggests that 'green exercise' (defined as physical activity in nature's environments) provides an important context for health-enhancing physical activity (HEPA), offering opportunities for (mental) health and well-being outcomes, compared to urban/manufactured environments. Theoretical explanations for HEPA tend to emphasize either nature's characteristics, or mental constructs, without explaining why similar behaviours have different outcomes in nature. Here, we discuss how an ecological dynamics rationale for this phenomenon simultaneously includes the environment and the individual. Design: A narrative position statement, based on a critical evaluation of the literature, and an ecological dynamics conceptualisation, was undertaken. Methods: The dominant theories were critically reviewed, and an ecological conceptualisation was proposed to highlight current limitations. Results: An ecological dynamics perspective adopts as its unit of analysis the person-environment system, where individuals and environments co-influence each other in a relational, transactional manner, rather than existing independently. An emphasis on the person-environment system suggests how elucidation of psychological processes needs to incorporate aspects of the environment. Thus, explanations of HEPA behaviours cannot be limited to processes considered to occur solely within the individual, implying the need for consideration of different affordances (behavioural opportunities) offered by a particular environment. Conclusions: Affordances in nature's environments are different from affordances in manufactured/urban contexts. Realizing such nature-based affordances implies perceptual and action variability that draws individuals to become, and remain, physically, psychologically and/or emotionally embedded in the natural environment. Highlights: The specific impact of HEPA in nature's environments benefits from a person-environment system's theoretical perspective. In such a transactional perspective, psychological processes incorporate aspects of the environment. Nature's affordances are less constrained than manufactured affordances. The natural environment, due to its variability, solicits embodied and embedded actions. Exerciser-nature interactions can be modulated by skill when solicited by affordances of nature.